How to find fraud and corruption : recipes for the aspiring fraud detective - Iyer, Nigel K. (London : Routledge, 2020)
In a typical working environment in which 'fraud and corruption' is as normal as a headache or as common as a cold, everyonein the organization has a role to play in finding and deterring fraudsters. Despite universal acknowledgement that these things may be illegal but still prevalent, managers still treat them as 'someone else's problem' or 'something that happens to other businesses, not ours'. This book shows, in simple terms, how everybody can become a successful fraud detective.A series of proven and easy-to-follow recipes show how to find the tell-tale signs of fraud and corruption and work with colleagues to deal withfraud smartly, keeping the organization you work for healthy and clean. The skills taught in this book are based on over 25 years' experience of successfully finding and dealing with fraud and corruption, all around the world. How to Find Fraud and Corruption offers wayfinding techniques for identifying and recognizing common frauds such as: suppliers who charge too much; sharp business partners and consultants who are taking you for a ride; customers who take but prefer not to pay. It also shows how to spot and unravel more complex but equally serious and common frauds: hidden connections to dirty money centres (the illegitimate side of tax havens); bribes paid as a shortcut to get business; creative numbers fraud (inflation of sales figures or suppression of costs); conflicts of interest involving individuals inside or outside the business. The final chapter is a short story (based on a real case) which illustrates a fraud detective's challenges,whether they are a reluctant whistleblower, someone who cannot turn a blind eye even if they would prefer to,or even the accused. Accessible and practical,this bookis for everyone who wants to stop fraud, including those working in accounting and finance, management, specialist functions, such as audit, compliance and security, and anyone else who aspires to be a fraud detective and stop fraud and corruption.
OCLC-licensed vendor bibliographic record.
Keywords: Commercial crimes; Corporations -- Corrupt practices; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Auditing